Morphodynamics of the Actin-Rich Cytoskeleton in Entamoeba histolytica - Manich, Maria; Hernandez-Cuevas, Nora; Ospina-Villa, Juan D.; Syan, Sylvie; Marchat, Laurence A.; Olivo-Marin, Jean-Christophe; Guillén, Nancy (Frontiers in Cellular and Infection Microbiology, 2018)
Entamoeba histolytica is the anaerobic protozoan parasite responsible for human amoebiasis, the third most deadly parasitic disease worldwide. This highly motile eukaryotic cell invades human tissues and constitutes an excellent experimental model of cell motility and cell shape deformation. The absence of extranuclear microtubules in Entamoeba histolytica means that the actin-rich cytoskeleton takes on a crucial role in not only amoebic motility but also other processes sustaining pathogenesis, such as the phagocytosis of human cells and the parasite’s resistance of host immune responses. Actin is highly conserved among eukaryotes, although diverse isoforms exist in almost all organisms studied to date. However, E. histolytica has a single actin protein, the structure of which differs significantly from those of its human homologs. Here, we studied the expression, structure and dynamics of actin in E. histolytica. We used molecular and cellular approaches to evaluate actin gene expression during intestinal invasion by E. histolytica trophozoites. Based on a three-dimensional structural bioinformatics analysis, we characterized protein domains differences between amoebic actin and human actin. Fine-tuned molecular dynamics simulations enabled us to examine protein motion and refine the three-dimensional structures of both actins, including elements potentially accounting for differences changes in the affinity properties of amoebic actin and deoxyribonuclease I. The dynamic, multifunctional nature of the amoebic cytoskeleton prompted us to examine the pleiotropic forms of actin structures within live E. histolytica cells; we observed the cortical cytoskeleton, stress fibers, “dot-like” structures, adhesion plates, and macropinosomes. In line with these data, a proteomics study of actin-binding proteins highlighted the Arp2/3 protein complex as a crucial element for the development of macropinosomes and adhesion plaques.